The Prosperity Gospel, the decolonisation of Theology, and the abduction of missionary imagination - Niemandt, Nelus (Missionalia: Southern African Journal of Missiology, 2017)
This research focussed on one of the most important social movements and contextual challenges in the African context – the explosive growth of the ‘prosperity gospel’ in Africa. It investigated this phenomenon from a missiological and African perspective, but in close relation to the discourses on decoloniality and decolonialisation, and asked if the prosperity gospel is a new form of colonialization. The research attended to the historical roots and theology of the prosperity gospel. It identified the core issue as one of contextualisation and investigated the prosperity gospel from a ‘glocal’ perspective. This brought the relationship between the prosperity gospel and globalisation (global) as well as local economic realities into the equation. Conclusions were made regarding the complex question whether the prosperity gospel can be regarded as a form of colonialization. The research found that the underlying epistemology is more oriented towards buttressing the worldview of global capitalism than deconstructing the political, social, and cultural domination established by Europeans and their Euro-North American descendants. It also concluded that the prosperity gospel is a spiritualisation of materiality and celebration of classic symbols of surplus/excess and consumerism. However, when attention was paid to local narratives and theologies, it became apparent that some prosperity churches have a strong focus on local communities and marginalised people and that leaders assisted in liberating empowering of members. The research concluded that this phenomenon might just lead to a particular form of African Pentecostalism that will, by itself, deconstruct coloniality and add exciting dimensions to the debate.
free
Keywords: Decoloniality; Prosperity gospel; decolonialisation; spiritualisation of materiality.